2019
DOI: 10.24349/acarologia/20194344
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature on a Chinese population of Amblyseius andersoni (Acari: Phytoseiidae) fed with Tetranychus urticae

Abstract: The development and fecundity of Amblyseius andersoni (Chant) fed with Tetranychus urticae Koch was studied at five different temperatures (17, 20, 25, 30 and 35 °C) and life parameters of the population were calculated. The development, reproduction, longevity, and life table parameters of A. andersoni were significantly affected by the different temperatures. The duration of the egg, larval, protonymph, deutonymph and total immature stages were reduced when the temperature increased. The total oviposition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
(33 reference statements)
1
9
0
Order By: Relevance
“…Nevertheless, the r m value of the predator population estimated by Lorenzon et al [35] on P. ulmi (0.175) was higher than that on P. taxi (0.166), which may result from the longer lifespan of females feeding on P. ulmi (over 40 days) than on P. taxi (28.3 days). It is worth noting that Lorenzon et al [35] conducted tests at a slightly higher temperature (24 • C) than in this study (23 • C) and many studies have shown that temperature significantly affects the life history of phytoseiid mites [86][87][88][89]. On the basis of the above comparison, we hypothesize that P. taxi is as valuable as prey for A. andersoni as the aforementioned species of spider mite pests of orchards or vineyards.…”
Section: Discussionsupporting
confidence: 48%
“…Nevertheless, the r m value of the predator population estimated by Lorenzon et al [35] on P. ulmi (0.175) was higher than that on P. taxi (0.166), which may result from the longer lifespan of females feeding on P. ulmi (over 40 days) than on P. taxi (28.3 days). It is worth noting that Lorenzon et al [35] conducted tests at a slightly higher temperature (24 • C) than in this study (23 • C) and many studies have shown that temperature significantly affects the life history of phytoseiid mites [86][87][88][89]. On the basis of the above comparison, we hypothesize that P. taxi is as valuable as prey for A. andersoni as the aforementioned species of spider mite pests of orchards or vineyards.…”
Section: Discussionsupporting
confidence: 48%
“…This is because this endophagous species is a polyphage, and a comprehensive list of the species it preys on has not been compiled. In addition, A. andersoni can be used over a wide range of temperatures from +17 °C to +35 °C (Li et al., 2019). It should be mentioned that the release rates of the predatory mite N. cucumeris were generally lower than the recommended ones during the entire observation period.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been reported by studies on other Typhlodromus and some phytoseiid species. These phytoseiid mites species can survive and develop even at extreme temperatures such as 15 and 35°C (Gotoh et al 2004; Li et al 2019; Ersin et al 2021); however, no development has been reported at temperatures below 15°C (de Vasconcelos et al 2008; Lee & Gillespie 2011). These results support that phytoseiid mites have wide temperature tolerances and are quite successful at more optimum temperatures.…”
Section: Discussionmentioning
confidence: 99%